SELECTIVITY OF LAMPUNG ZEOLITE TOWARDS MATRICES CATIONS GENERATED FROM URANIUM FISSION - Amini, Siti; Anggraini, Dian; Nampira, Yusuf; Rosika, Rosika; Noviarti, Noviarti; Nugroho, Arif (Jurnal Zeolit Indonesia, 2003)
Selectivity of zeolite-lampung (ZKK) towards some matrices cations generated from uranium fission products has been investigated using some typical fission product-non-radioactive cations by cation exchange batch-system process. The previous investigation showed that zeolite-lampung is effectively able to absorb cesium ion from radioactive waste, consequently the presence of others cations i.e. generated cations from the uranium fission products are assumed as the competitive cations which may affect the zeolite selectivity on to Cs exchanges, on the otherhand the Cs-exchange capacity of zeolite would decrease. The main matrices cations which present in the natural zeolite are K+, Na+ and Ca2+and those are generated from fission products such as Cs+, Ba2+, Sr2+ and Ce4+ exist in the nuclear spent fuel solution. The ion exchanges of counterpart cations in zeolites with that each of Cs+, Ba2+, Sr2+ and Ce4+ ion or/and its mixtures have been examined. The selectivity of zeolite onto mentioned exchanged cations has been shown by the correlation of fraction of the cations concentration in the zeolite (Az) towards that in equilibrated solution (As). The results show that the raw zeolite Lampung selectivity is decrease in order to Cs+> Ba2+= Sr2+ > Ce4+. The exchanged capacity of zeolite into Cs+ ion is decreased by the presence of combining ions of Ba2+, Sr2+ and Ce4+, and so are those competitive cations.